Thromboembolic Complications in Cardiovascular Diseases: Pathophysiological Mechanisms and Modern Approaches to Prevention - Ortiq o’g’li, Raupov Abdurahmon (Journal of Innovation in Education and Social Research, 2025)
The development of thromboembolic complications in cardiovascular diseases (CVDs) is primarily associated with atherothrombosis, characterized by the rupture, fissure, or erosion of atherosclerotic plaques and subsequent thrombus formation. Thromboembolic events can occur in both arterial and venous circulations, significantly increasing morbidity and mortality among CVD patients. Intracardiac thrombosis frequently accompanies atrial fibrillation, myocardial infarction, and valvular defects. The main strategy for preventing atherothrombosis and thromboembolic complications involves the rational use of antiplatelet agents and anticoagulants. Numerous clinical studies and meta-analyses have confirmed the efficacy of antiplatelet therapy, particularly dual antiplatelet therapy (DAPT) combining acetylsalicylic acid (ASA) and clopidogrel, in reducing cardiovascular events by approximately 25%. The combined use of anticoagulants (such as warfarin) and antiplatelet drugs is especially indicated in patients with high thromboembolic risk, including those after stent implantation or with atrial fibrillation. However, the intensification of antithrombotic therapy increases the risk of gastrointestinal adverse reactions, including erosive and ulcerative lesions and bleeding. Therefore, an individualized, risk-balanced approach to combination therapy is essential to optimize efficacy and minimize complications.